2017
DOI: 10.4236/ojps.2017.74038
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Smoking Habits and Self-Rated Health of Older Persons in the Philippines: Evidence-Based Tobacco Policy Advocacy

Abstract: Tobacco is one of the risk factors for non-communicable disease. The Philippines's smoking rate of aged 15 years and older is 23.8%, which is high in Asian countries. This study aimed to investigate whether older persons' smoking habits are associated with lower self-rated health (SRH) and advocate for policy amendment in the Philippines. This research conducted a cross-sectional study on 300 eligible Filipinos aged 60 and over living in Metro Manila, Quezon City, from November 2012 to March 2013. The number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
1
1
0
1
Order By: Relevance
“…The study sustained findings form previous research that better SRH was reported among people who smoked cigarettes and consumed alcohol [ 27 ]. However, this finding contradicted an earlier study that associated smoking and drinking with lower SRH scores [ 28 ] and another that found that the elderly with healthier lifestyles believed themselves to be healthier than those with less healthy lifestyles [ 29 ].…”
Section: Discussionsupporting
confidence: 87%
“…The study sustained findings form previous research that better SRH was reported among people who smoked cigarettes and consumed alcohol [ 27 ]. However, this finding contradicted an earlier study that associated smoking and drinking with lower SRH scores [ 28 ] and another that found that the elderly with healthier lifestyles believed themselves to be healthier than those with less healthy lifestyles [ 29 ].…”
Section: Discussionsupporting
confidence: 87%
“…El presente estudio no identificó una implicación entre tabaquismo y consumo de bebidas alcohólicas con la salud autoevaluada. Al respecto, un estudio previo afirmó que fumar y consumir bebidas alcohólicas favorecen una mejor salud autoevaluada en personas adultas mayores (Kashiwagi, 2017); sin embargo, otras investigaciones lo refutan (Wang et al, 2018).…”
Section: Discussionunclassified
“…Several determinants that affect smoking behavior in people in developing countries such as the Gender, education level, income per capita, ownership of health insurance, and occupational factors are several determinants of smoking behavior among people in developing countries such as the Philippines 10 . We also know that smoking behavior is because of social pressure at work, physical activity disorders, sleeping di culties 10,11 . A study on smoking behavior in Indonesian women as a risk factor for breast cancer has been conducted by 12 .…”
Section: Introductionmentioning
confidence: 99%